2016
DOI: 10.1111/irv.12378
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association of TLR4 Asp299Gly, TLR4 Thr399Ile, and CD14 C‐159T polymorphisms with the risk of severe RSV infection: a meta‐analysis

Abstract: Respiratory syncytial virus (RSV) is the most frequent cause of hospitalization in infants worldwide. It is recognized by Toll‐like receptor 4 (TLR 4) and cluster of differentiation 14 (CD14) in the innate immune response. Previous case–control studies reported the influence of TLR4 Asp299Gly, TLR4 Thr399Ile, and CD14 C‐159T polymorphisms on the risk of severe RSV infection. However, a decisive conclusion has not been achieved. Therefore, we performed this meta‐analysis to examine the association between these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…The TLR4 rs4986790 was studied also in our Finnish bronchiolitis cohort without any significant association with bronchiolitis or post‐bronchiolitis asthma. Our negative results were in agreement with the negative result of another Finnish study that comprised 312 bronchiolitis cases and 356 controls and the conclusions of a meta‐analysis that focused on six studies and more than 1000 bronchiolitis patients .…”
Section: Discussionmentioning
confidence: 99%
“…The TLR4 rs4986790 was studied also in our Finnish bronchiolitis cohort without any significant association with bronchiolitis or post‐bronchiolitis asthma. Our negative results were in agreement with the negative result of another Finnish study that comprised 312 bronchiolitis cases and 356 controls and the conclusions of a meta‐analysis that focused on six studies and more than 1000 bronchiolitis patients .…”
Section: Discussionmentioning
confidence: 99%
“…TLR4 and CD14 are involved in the innate immune sensing of RSV infection and induction of inflammatory mediators and were thus among the first proteins to be predicted to be associated with disease severity. Although some investigations observed correlations between CD14 and TLR4 polymorphisms and RSV bronchiolitis, recent meta-analysis of multiple studies indicates a lack of association (64, 91, 123, 178). …”
Section: Respiratory Syncytial Virusmentioning
confidence: 97%
“…[80][81][82][83][84][85] However, in a meta-analysis, Zhou et al reported that all of these polymorphisms are not associated with the risk of severe RSV infection. 86 These results indicate that, in different ethnic groups, different genetic factors contribute to the development of RSV bronchiolitis.…”
Section: Effects Of Variation In Pattern Recognition Receptorsmentioning
confidence: 91%
“…Some studies supported a positive association between these SNPs and severe RSV bronchiolitis, while others could not replicate this association . However, in a meta‐analysis, Zhou et al reported that all of these polymorphisms are not associated with the risk of severe RSV infection . These results indicate that, in different ethnic groups, different genetic factors contribute to the development of RSV bronchiolitis.…”
Section: Introductionmentioning
confidence: 99%